"Understanding Literature Reviews from Narrative to Meta-Analysis: Frameworks, Typologies, and Writing Styles" (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: A literature review is a critical intellectual activity that highlights gaps in knowledge, places new research in the perspective of what is already known, and guides future study. The objective, technique, advantages, and disadvantages of the main categories of literature reviews—narrative, systematic, and critical reviews—are examined in this essay. While systematic reviews adhere to strict, repeatable protocols to reduce bias, narrative reviews offer comprehensive, descriptive summaries of findings. By combining quantitative results using statistical methods, meta-analyses expand on systematic reviews and improve the validity and generalisability of findings. Finding methodological or conceptual flaws in earlier research is the main goal of critical reviews. Along with discussing writing styles such as contextual, variable-based, and methodological organisation, the study highlights the significance of summarising local, national, and worldwide research to show its applicability.